Symphony No. 6 in F Major, Op. 68 Pastorale - Beethoven, Ludwig van. 1770-1827 (Colección Dover Miniature Scores, 1998)
Beethoven's profound love of nature, nourished by his solitary rambles through the countryside, provided the wellspring for his sixth symphony. Five years in the making, the "Pastorale" particularly reflects his feelings for rustic pleasures, and performers and listeners rejoice in a work more nuanced and delicate than the composer's typically intense symphonies. The music is reproduced here from an authoritative edition, with bar-numbered movements and ample margins at the bottom of each score page for notes and analysis. Ideal for study in the classroom, at home, or in the concert hall, this affordable high-quality, conveniently sized volume will be the edition of choice for music students and music lovers alike.